Diversity of Undergrowth in Teak Forest Areas as a Feed Source Bali Cattle in Watopute District - Damhuri, Damhuri; Lili Darlian, Lili; Marnitasari, Marnitasari; Aku, Achmad Selamet; Auza, Fuji Astuty; Zulkarnain, Deki; Tasse, Andi Murlina (Universitas Halu Oleo, 2023)
ABSTRACT Indonesia has tropical rainforests that are so vast and have a diversity of plants. The study aimed to identify the diversity of undergrowth in the teak forest area as a source of fodder for Bali cattle in Watopute District, Muna Regency, to be carried out in August–December 2022 with purpose location determination and village surveys using stratified random sampling based on area criteria low, medium, and high. Data collection used the field observation method by exploring and taking samples using a 10x30 m2 transect. The research variables included observations of plant species in the teak forest area and forage plant species in the teak forest area, which were then analyzed using the summed dominance ratio formula. The results of research on plant species in the teak forest area show that there are 17 families with 43 species, and for plant species that can be used as a source of feed for breeders, there are as many as 16 species. From the research, it can be concluded that livestock looking for food in the teak forest area in Watopute District consists of 16 plant species.Keywords: plants, teak forest, bali cattle, watopute